Microwave-Assisted Synthesis and Antioxidant Evaluation of α,β-Unsaturated Ketones Incorporating a Pyrano[3,2-g] Chromene-2,6-dione Core via Claisen–Schmidt Condensation - Nguyen, Ngoc Thanh; Pham, Thi Thu Giang; Ngo, Thuy Van (Trends in Sciences, 2025)
A green, rapid and high-yielding microwave-assisted synthesis of α,β-unsaturated ketones from pyrano[3,2-g]chromene derivatives was developed, followed by preliminary structure–activity relationship (SAR) evaluation. Inspired by the broad pharmacological potential of chromone-based scaffolds, these analogues were designed to enhance antioxidant properties. The key intermediate, 7-acetyl-4,8-dimethyl-2H,6H-pyrano[3,2-g]chromene-2,6-dione, was obtained via a Kostanecki–Robinson reaction and subsequently transformed through Claisen–Schmidt condensations with diverse aromatic aldehydes under microwave irradiation, affording twelve target compounds (6a–6l) in excellent yields (74% - 95%) within minutes. Structural identities were confirmed by spectroscopic and mass analyses. Antioxidant screening using the DPPH assay identified derivative 6 g as the most potent, exhibiting 86.7% radical scavenging at 50 µM, comparable to ascorbic acid (97.65%). While only a DPPH assay was performed, these results provide preliminary antioxidant insights that warrant further biological validation. HIGHLIGHTS An efficient green synthesis affords novel α,β-unsaturated ketones with a pyrano[3,2-g]chromene-2,6-dione core. Microwave irradiation dramatically reduces reaction time to 10 min for the key step, delivering high yields (74% - 95%). Antioxidant potency is governed by phenolic substituents, with derivative 6g exhibiting strong activity (86.7% inhibition), rivaling ascorbic acid. A clear SAR emerges: para-hydroxy groups enhance activity, while ortho-substitution diminishes it due to intramolecular H-bonding. GRAPHICAL ABSTRACT